Effects of Duloxetine in Rats Trained to Discriminate Between 2 and 22 hr Food Deprivation - Nemec, Dillon J.; Reed, Krystal A.; Vanden Avond, Mark A.; Lucas, A. L.; Johnson, Amy R.; Toddes, Carlee; Vossen, Taylor J.; Hendrickson, Elizabeth J.; Schultz, Andrew T. (My University, 2013)
Duloxetine inhibits serotonin and norepinephrine transporters, and is clinically used to treat depression, pain, and generalized anxiety disorder. Duloxetine has been shown to reduce food intake in several species. The purpose of this study was to examine the effects of duloxetine in non-restricted rats trained to discriminate between 22- and 2-hour food deprivation to gain better understanding of neurochemicals mediating the discriminative stimulus e ects of 22-hour food deprivation.
Color poster with text, graphs, and tables.
Keywords: Duloxetine--Side effects; Posters; Discrimination learning; Hunger--Psychological aspects; Rats--Training